The Pupal Ectoparasitoid Pachycrepoideus vindemmiae Regulates Cellular and Humoral Immunity of Host Drosophila melanogaster - Yang, Lei; Wan, Bin; Wang, Bei-Bei; Liu, Ming-Ming; Fang, Qi; Song, Qi-Sheng; Ye, Gong-Yin (Frontiers in Physiology, 2019)
The immunological interaction between Drosophila melanogaster and its larval parasitoids have been thoroughly investigated, however little is known about the interaction between the host and its pupal parasitoids. Pachycrepoideus vindemmiae, a pupal ectoparasitoid of D. melanogaster, injects venom into its host while laying eggs on the puparium, which regulates host immunity and interrupts host development. To resist the invasion of parasitic wasps, various immune defense strategies have been developed in their hosts as a consequence of the co-evolution. In this study, we mainly focused on the host immunomodulation by P. vindemmiae and thoroughly investigated cellular and humoral immune response, including cell adherence, cell viability, hemolymph melanization and the Toll, Imd, JAK/STAT immune pathways. Our results indicated that venom had a significant inhibitory effect on lamellocyte adherence and induced plasmatocyte cell death. Venom injection and in vitro incubation strongly inhibited hemolymph melanization. More in-depth investigation revealed that the Toll and Imd immune pathways were immediately activated upon parasitization, followed by the JAK/STAT pathway, which was activated within the first 24 h post-parasitism. These regulatory effects were further validated by qPCR. Our present study manifested that P. vindemmiae regulated the cellular and humoral immune system of host D. melanogaster in many aspects. These findings lay groundwork for studying the immunological interaction between D. melanogaster and its pupal parasitoid.